Associations and political participation of people with disabilities: the case of associations participating in the German disability council - Schaefer, Márcia Inês (Revista Debates, 2025)
The study presents data on political participation activities carried out between 2014 and 2023 by associations that are part of the German Disability Council. The text begins with a literature review on barriers to the political participation of persons with disabilities, followed by a brief history of this type of association in Germany. The data was mapped by analyzing the associations' statutes, websites, and official social media pages. The main objectives of the associations are to represent the interests of persons with disabilities and rare/chronic diseases; improve the quality of life and the dissemination of information, production of knowledge, and support for research and science. There is significant political participation, with presence in central deliberation spaces in the formulation of disability policies, working in networks, and monitoring the implementation of the Convention on the Rights of Persons with Disabilities in Germany. Keywords: associations, political participation, persons with disabilities, CRPD, German Disability Council.